Spatial distribution mapping of molecules in the grains of different rice landraces, using desorption electrospray ionization mass spectrometry. (5th March 2019) - Suganya, Arunan; Deb, Debal; Pradeep, Thalappil
Abstract : Rationale: Documentation of the metabolite profiles of rice landraces is essential as most of them have been lost due to the conventional practices of cultivation. Therefore, application of mass spectrometry imaging (MSI) will be an appropriate analytical platform for molecular profiling, as it can provide a detailed understanding of the site‐specific localization patterns of biomolecules, and the cues concerning metabolic pathways in organisms. Methods: Desorption electrospray ionization mass spectrometry (DESI‐MS) is a relatively non‐destructive analytical technique for surface sampling in natural conditions. Here, we report the spatial distribution of diverse molecules in the grains of different rice landraces of India using DESI‐MSI. Molecules were identified by ESI‐MS and tandem MS analysis of rice extracts. Scanning electron microscopy (SEM) and energy‐dispersive X‐ray spectroscopy (EDS) were used for the elemental mapping on the rice grains. Results: DESI‐MSI showed a uniform distribution of choline ( m/z 104.1), sucrose in the form of its sodium ( m/z 365.1) and potassium ( m/z 381.0) adducts, linoleic acid ( m/z 279.2), 13‐HODE‐9‐HODE ( m/z 295.2), unidentified molecules with m/z 535.3, 559.5, and 561.5 and isoschaftoside ( m/z 563.1) in the endosperm of rice grains. Gluconic acid ( m/z 195.0) and signalling phospholipid intermediate molecules were localized in the embryo whereas oryzanol A ( m/z 601.5) and oryzanol C ( m/z 615.5) had a restricted localization in the bran region of the grain. SEM‐EDS mapping showed the localization of potassium and phosphorus along the bran and embryo. Conclusions: DESI‐MSI revealed the distribution of lipids and sugar molecules in the specific regions of the rice grains. Thus, molecules unique to some rice varieties were identified with this analytical platform. Mass spectrometry imaging of rice along with the elemental mapping by SEM‐EDS will be of use in understanding the localization pattern of certain molecules in the context of metals present in the grain.